Tindak Pidana Perdagangan Blackmarket Menurut UU No 17 Tahun 2006 tentang Kepabeanan Dan Hukum Pidana Islam - Rahmadani, Windy; Khosim, Ali; Azazy, Yusuf (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
Blackmarket trade is an illegal activity that bypasses official customs systems and harms the state economically, legally, and socially. This study aims to examine blackmarket crimes based on Law No. 17 of 2006 concerning Customs and from the perspective of Islamic criminal law. The method used is library research with a normative juridical approach, analyzing relevant regulations, concepts, and legal principles. Findings indicate that blackmarket actors face penalties including imprisonment and fines under Articles 102-104 of the Customs Law. From the Islamic criminal law perspective, blackmarket trade is categorized as jarimah ta’zir because it harms society and contradicts principles of justice and economic honesty. Thus, this practice violates both positive law and Islamic law, requiring firm law enforcement and moral education to prevent it.